The Influence of Training, Education and Motivation of Superiors on The Usefulness of The Regional Financial Accounting System in The Sidoarjo Regency Education and Training Staffing Agency - Pudjo Santosa, Herlambang (Institute of Computer Science (IOCS), 2022)
This study aims to empirically test the extent to which training, education, and motivation of superiors affect the usefulness of the regional financial accounting system at the government office of BPKKD Sidoarjo Regency. The population in this study is all employees of the finance department of 135 people in Sidoarjo regency, with the number of samples needed as many as 57 respondents. The data obtained will be analyzed using multiple linear regression.After knowing the problem, researching and discussing the results of the study, several conclusions can be drawn as follows: Based on test F shows that Training, Education and Motivation of Superiors affect the Usefulness of SAKD, so that the regression model produced is suitable or appropriate in explaining the Usefulness of SAKD. Based on partial tests for variables, training partially has no effect on the usefulness of SAKD. Based on partial tests for variables Education partially has no effect on the usefulness of SAKD. Based on partial tests for the Superior Motivation variable partially affects the Usefulness of SAKD.